Physical Activity Training Methods to Improve the Physical Condition of Volleyball Players: A Systematic Review - Gatot Jariono; Nurhidayat; Pungki Indarto; Vera Septi Sistiasih; Haris Nugroho; Uzizatun Maslikah (OVS LLC, 2024)
Study purpose. The study was aimed to identify exercise techniques used to improve the physical condition of volleyball players through literature studies. Materials and methods. A systematic review of these previous studies was conducted. We studied articles published between 2014 and 2023 that explained how to prepare volleyball players to have better physical condition. Scopus, Web of Science, Google Scholar, and PubMed were used for the electronic search. We collected all the articles that discussed how to improve physical performance through exercise. Results. To improve the physical condition of volleyball players, 50 publications used exercise techniques, which were categorized based on the physical condition that was evaluated and repaired. The following techniques are some of the ones that can be used: Neuromuscular, unilateral and bilateral, ballistic, plyometric exercises, combined weight and plyometric, mixed training with optimal load, COD & plyometric complex, strength, combined strength, eccentric trainings, repetitive sprint, resistant/non-resistant sprint, resistance training, exercises with elastic band, core training, combined core training; small-sided games training, aerobic interval training, blood flow restriction, intermittent training, and anaerobic speed endurance. Conclusions. Following a thorough analysis, a number of training regimens were found to be effective in enhancing volleyball players' physical attributes, including muscular strength, aerobic and anaerobic endurance, speed and acceleration, explosive power, flexibility, agility, and balance.